Factors Associated with Work Performance and Mental Health of Healthcare Workers During Pandemics In Asia : a Systematic Review - Almira Dova, Syarifah; Oktamianti, Puput (Syntax Literate, 2023)
COVID-19 is highly contagious and the transmission dynamics are associated with intercontinental spread. The pandemic’s short-term and long-term impact on healthcare worker’s mental health and well-being remains largely unknown. This systematic review used preferred reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The articles were searched from PubMed, the reviewers had screened 729 abstracts, 372 full-text publications, and ultimately included 11 systematic reviews. The review found ten factors associated with the work performance and mental health of healthcare workers in Asia, including experiencing feelings of anxiety, having inadequate support, depression, experiencing occupational stress, loneliness, lack of workplace preparedness, financial concerns associated with changes in income and daily living, fear of transmission, burnout/fatigue and sleep disturbance. This systematic review can be used as input for governments and employers as a reference to develop strategies to support healthcare workers’ mental health, well-being and work productivity.